Causal Interactions between Frontal(θ) – Parieto-Occipital(α2) Predict Performance on a Mental Arithmetic Task - Dimitriadis, Stavros I. (Front Hum Neurosci, 2016)
Many neuroimaging studies have demonstrated the different functional contributions of spatially distinct brain areas to working memory (WM) subsystems in cognitive tasks that demand both local information processing and interregional coordination. In WM cognitive task paradigms employing electroencephalography (EEG), brain rhythms such as θ and α have been linked to specific functional roles over given brain areas, but their functional coupling has not been extensively studied. Here we analyzed an arithmetic task with five cognitive workload levels (CWLs) and demonstrated functional/effective coupling between the two WM subsystems: the central executive located over frontal (F) brain areas that oscillates on the dominant θ rhythm (Frontal(θ)/F(θ)) and the storage buffer located over parieto-occipital (PO) brain areas that operates on the α(2) dominant brain rhythm (Parieto-Occipital(α2)/PO(α2)). We focused on important differences between and within WM subsystems in relation to behavioral performance. A repertoire of brain connectivity estimators was employed to elucidate the distinct roles of amplitude, phase within and between frequencies, and the hierarchical role of functionally specialized brain areas related to the task. Specifically, for each CWL, we conducted a) a conventional signal power analysis within both frequency bands at F(θ) and PO(α2), b) the intra- and inter-frequency phase interactions between F(θ) and PO(α2), and c) their causal phase and amplitude relationship. We found no significant statistical difference of signal power or phase interactions between correct and wrong answers. Interestingly, the study of causal interactions between F(θ) and PO(α2) revealed frontal brain region(s) as the leader, while the strength differentiated between correct and wrong responses in every CWL with absolute accuracy. Additionally, zero time-lag between bilateral F(θ) and right PO(a2) could serve as an indicator of mental calculation failure. Overall, our study highlights the significant role of coordinated activity between F(θ) and PO(α2) via their causal interactions and the timing for arithmetic performance.